DECISION SUPPORT SYSTEM FOR WI-FI MODEM SELECTION USING MULTIPLE ATTRIBUTE DECISION MAKING WITH TOPSIS - Nur Sucahyo; Ahmad Fitriansyah; Yogasetya Suhanda (Kresnamedia Publisher, 2022)
The modem is a device that can connect mobile phones, PCs, or laptops to the internet network. The modem popular today is MiFi or Wi-Fi Modem, a portable modem that makes it easier for users to carry the device anywhere. Many Wi-Fi modems are circulating in the market with various brands with different specifications and capabilities. For this reason, people must be observant in choosing the right Wi-Fi Modem for their needs. Selection of the right Wi-Fi Modem will maximize the internet network's performance to facilitate internet use activities. This study aims to develop a decision support system by implementing the Multiple Attribute Decision Making (MADM) approach using the TOPSIS method for selecting a Wi-Fi Modem to facilitate the selection of the best Wi-Fi Modem according to user needs. Based on black-box testing, it shows that the system built can run well. In addition, the calculation results of the TOPSIS method generated by the system with manual calculations produce the same value.